2016
DOI: 10.1186/s40463-016-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

An outcomes analysis of anterior epistaxis management in the emergency department

Abstract: BackgroundMany treatment options exist for the management of anterior epistaxis. However, little is known about treatment outcomes. The objective was to identify the currently utilised methods of management and outcomes for patients with anterior epistaxis presenting to the emergency department (ED) at a Canadian tertiary care center.MethodsA retrospective review of ED visits from January 2012-May 2014 for adult patients with a diagnosis of anterior epistaxis was performed. Patient demographic data, comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 11 publications
3
35
0
2
Order By: Relevance
“…In this present study, we followed a cohort of patients aged 70 years until they reached a life expectancy of the Canadian population of 82 years . The mean age of 70 years was consistent with that reported in a published study describing the baseline and clinical characteristics of patients with acute anterior epistaxis who visited the Ottawa Hospital . A cycle length of 1 year was used.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…In this present study, we followed a cohort of patients aged 70 years until they reached a life expectancy of the Canadian population of 82 years . The mean age of 70 years was consistent with that reported in a published study describing the baseline and clinical characteristics of patients with acute anterior epistaxis who visited the Ottawa Hospital . A cycle length of 1 year was used.…”
Section: Methodsmentioning
confidence: 89%
“…In a setting where healthcare funding is limited, there is growing evidence that both costs and effectiveness should be considered when choosing a modality of treatment . Although there is no particular algorithm for the treatment of epistaxis, physicians in EDs in Canada frequently use nasal packing to treat anterior epistaxis . There are a variety of different types of nasal packing, which typically have a low unit cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used chemical agent is silver nitrate, but there are also reported cases of chemical cauterization with trichloroacetic acid or chromic acid 18 . Newton et al, in a retrospective study published in April 2016, analysed the effectiveness of different anterior epistaxis treatment methods performed in the Emergency Department (silver nitrate cauterization, petroleum gauze packing, Merocel®, nasal clip or simple observation) 19 . They concluded that cauterization with silver nitrate returned best results in terms of recurrence and follow-up, compared to the Merocel® packing and petroleum gauze packing outcomes.…”
Section: Primary Intention Treatment Methodsmentioning
confidence: 99%
“…Although prior studies have characterized demographic, seasonal, and geographic variation in epistaxis presentation throughout the United States, there is a limited understanding of contemporary management patterns in the ED setting . Indeed, as epistaxis management has evolved, so too has the landscape of emergency care.…”
Section: Introductionmentioning
confidence: 99%